Vaso-Occlusive Pain and Menstruation in Sickle Cell Disease: A Focus Group Analysis - Melissa Day; Kemberlee Bonnet; David G. Schlundt; Michael DeBaun; Deva Sharma (Mary Ann Liebert, 2020)
Background: Acute vaso-occlusive pain, herein referred to as acute sickle cell disease (SCD) pain, associated with menstruation has received little attention. Key unanswered questions include how women differentiate acute SCD pain and menstrual cramps, and how both types of pain impact quality of life. Methods: Using inductive/deductive qualitative research methods, three focus groups were conducted to understand the patient experience of acute SCD pain associated with menstruation. Results: Fourteen women with SCD participated in our focus groups. Major themes were identified: (1) clinical sequelae of SCD surrounding menstruation, (2) coping with psychosocial challenges, (3) interpersonal difficulties and support systems, (4) impacts on quality of life, (5) impacts on emotional well-being, and (6) proposed solutions for health care systems. Conclusions: Women with SCD can distinguish acute SCD pain from menstrual cramps. Health care providers should become more familiar with acute SCD pain associated with menstruation and encourage a patient-centered dialogue to determine appropriate courses of action.